Altered parasite community structure in an endangered marsupial following translocation. (December 2019) - Northover, Amy S.; Thompson, R.C. Andrew; Lymbery, Alan J.; Wayne, Adrian F.; Keatley, Sarah; Ash, Amanda; Elliot, Aileen D.; Morris, Keith; Godfrey, Stephanie S.
Abstract: Fauna translocations play an integral role in the management of threatened wildlife, though we are limited by our understanding of how the host-parasite community changes during translocation. During this longitudinal field-based study, we monitored gastrointestinal, blood-borne and ectoparasite taxa infecting woylies ( Bettongia penicillata ) for up to 12 months following two fauna translocations to supplement existing wild woylie populations in three different sites (Dryandra, Walcott and Warrup East) within the south-west of Western Australia. We aimed to (a) identify changes in parasite community structure of both translocated and resident woylies following translocation; and (b) evaluate the efficacy of ivermectin treatment in translocated hosts. Destination site and time since translocation had the strongest effects on parasite prevalence and mean faecal egg counts following translocation. Ivermectin treatment did not significantly reduce parasite prevalence or mean faecal egg counts in treated hosts. Prior to translocation, parasite community composition differed significantly between woylies selected for translocation and resident woylies within each release site. Following translocation, the parasite communities of translocated and resident hosts converged to become more similar over time, with loss of parasite taxa and novel host-parasite associations emerging. This is the first study to examine changes to the broader parasite community in translocated and resident animals following translocation. The dominant site-specific response of parasites following translocation reinforces the importance of incorporating parasite studies to enhance our fundamental understanding of perturbations in host-parasite systems during translocation, in particular the site-level drivers of parasite dynamics. Graphical abstract: Image 1 Highlights: Perturbations to host-parasite systems during translocation are poorly understood. Parasite dynamics were strongly impacted by site and time since translocation. The parasite communities of translocated and resident hosts converged over time. Ivermectin treatment had no significant impact on target parasites. Translocation protocols should consider the intrinsic biodiversity value of parasites.